Choice and Procrastination - O'Donoghue, T.; Rabin, M. (Quarterly Journal of Economics, 2001)
Recent models of procrastination due to self-control problems assume that a procrastinator considers just one option and is unaware of her self-control problems. We develop a model where a person chooses from a menu of options and is partially aware of her self-control problems. This menu model replicates earlier results and generates new ones. A person might forgo completing an attractive option because she plans to complete a more attractive but never-to-be-completed option. Hence, providing a nonprocrastinator additional options can induce procrastination, and a person may procrastinate worse pursuing important goals than unimportant ones.